Phenolic Profiles and Contribution of Individual Compounds to Antioxidant Activity of Apple Powders. Issue 5 (22nd March 2016) - Raudone, Lina; Raudonis, Raimondas; Liaudanskas, Mindaugas; Viskelis, Jonas; Pukalskas, Audrius; Janulis, Valdimaras
Abstract: Apples ( Malus domestica L.) are the most common source of phenolic compounds in northern European diet. Besides pectins, dietary fibers, vitamins, and oligosaccharides they contain phenolic compounds of different classes. Apple powders are convenient functional forms retaining significant amounts of phenolic antioxidants. In this study reducing and radical scavenging profiles of freeze‐dried powders of "Aldas, ˮ "Auksis, ˮ "Connel Red, ˮ "Ligol, ˮ "Lodel, ˮ and "Rajkaˮ were determined and phenolic constituents were identified using ultra high‐performance liquid chromatography coupled to quadrupole and time‐of‐flight mass spectrometers. A negative ionization mode was applied and seventeen compounds: phenolic acids (coumaroylquinic, chlorogenic), flavonoids (quercetin derivatives), and procyanidin derivatives (B1, B2, and C1) were identified in all tested apple samples. Total values of Trolox equivalents varied from 7.72 ± 0.32 up to 20.02 ± 0.52 and from 11.10 ± 0.57 up to 21.42 ± 0.75 μmol/g of dry weight of apple powder in FRAP (ferric reducing antioxidant power) and ABTS (2, 2‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulfonic acid) postcolumn assays, respectively. The greatest Trolox equivalent values were determined for apples of "Aldasˮ cultivar. Chlorogenic acid and procyanidin C1 were the most significant contributors to total reducing and radical scavenging activity in all apple cultivars tested, therefore they could be considered as markers of antioxidant activity.